2010
DOI: 10.1111/j.1095-8312.2010.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of an alpine shrub Hippophae tibetana (Elaeagnaceae): allopatric divergence and regional expansion

Abstract: Increasing evidence suggests that geological or climatic events in the past promoted allopatric speciation of alpine plants in the Qinghai-Tibetan Plateau and adjacent region. However, few studies have been undertaken to examine whether such allopatric divergences also occurred within a morphologically uniform species. In the present study, we report the evolutionary history of an alpine shrub species, Hippophae tibetana, based on examining chloroplast DNA (cpDNA) and nuclear ribosomal internal transcribed spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
85
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 63 publications
17
85
2
1
Order By: Relevance
“…Deep divergences within this species seem to have started since the late Pleistocene, which is in accord with conclusions from numerous studies of other species in this region (e.g., Liu et al, 2002;Wang et al, 2009a;Jia et al, 2011). Moreover, we thought that this kind of deep divergence within O. thoroldii may possibly be as a result of adaption to the origin of divergent aridity habitats, whose mechanism is similar to some previous studies of other arid/desert species Wang et al, 2013;Meng et al, 2014).…”
Section: Glacial Refugia and Demographic Expansionsupporting
confidence: 92%
See 1 more Smart Citation
“…Deep divergences within this species seem to have started since the late Pleistocene, which is in accord with conclusions from numerous studies of other species in this region (e.g., Liu et al, 2002;Wang et al, 2009a;Jia et al, 2011). Moreover, we thought that this kind of deep divergence within O. thoroldii may possibly be as a result of adaption to the origin of divergent aridity habitats, whose mechanism is similar to some previous studies of other arid/desert species Wang et al, 2013;Meng et al, 2014).…”
Section: Glacial Refugia and Demographic Expansionsupporting
confidence: 92%
“…For example, some species that were sensitive to these climate changes retreated from eastern refugia during the glacial stage and re-colonized the central plateau platform (e.g., Zhang et al, 2005;Chen et al, 2008;Yang et al, 2008). However, other cold-tolerant species were able to survive in situ during glacial periods in ice-free microrefugia (Wang et al, 2009a;Opgenoorth et al, 2010;Jia et al, 2011). In such situations, independent genetic lineages appeared in different plateau regions due to isolations among developed ice sheets.…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency of private ribotypes in seeder populations can neither be explained by geographic isolation, since average pairwise geographic distances are actually shorter in seeder than in resprouter populations (Segarra-Moragues and Ojeda 2010), and both seeder and resprouter forms have equal pollination and seed dispersal traits (Malan 2013). A high frequency of private ribotypes has also been suggested as a signature of accelerated ITS evolution (see Jia et al 2011). Interestingly, our results parallel the higher frequency of private microsatellite alleles in E. coccinea seeder populations reported by Segarra-Moragues and Ojeda (2010), which these authors interpreted as the result of faster rates of new alleles arising in seeder populations owing to their comparatively shorter generation times.…”
Section: Discussionsupporting
confidence: 89%
“…increased rate of molecular change-in different taxa (e.g. SegarraMoragues and Ojeda 2010; Jia et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have also indicated that within different allopatric regions, patterns of range shift have been distinct; in some regions, range expansion might have occurred. For example, in the eastern Qinghai-Tibetan Plateau (QTP), most populations of Allium przewalskianum contained multiple haplotypes and showed significant genetic divergence from each other, but in the western QTP, this species experienced an earlier range expansion at the end of the last glacial maximum (LGM) (Wu et al 2010); two distinct lineages of Hippophae tibetana were found distributed in eastern and western regions of the QTP, but within each, populations had experienced a recent postglacial expansion (Jia et al 2011). For those species which are in decline, the identified differentiated populations should be taken into consideration for conservation measures.…”
Section: Introductionmentioning
confidence: 99%